Does area V3A predict positions of moving objects? - Maus, Gerrit W.; Weigelt, Sarah; Nijhawan, Romi; Muckli, Lars (Frontiers in Psychology, 2010)
A gradually fading moving object is perceived to disappear at positions beyond its luminance detection threshold, whereas abrupt offsets are usually localised accurately. What role does retinotopic activity in visual cortex play in this motion-induced mislocalization of the endpoint of fading objects? Using functional magnetic resonance imaging (fMRI), we localised regions of interest (ROIs) in retinotopic maps abutting the trajectory endpoint of a bar moving either towards or away from this position while gradually decreasing or increasing in luminance. Area V3A showed predictive activity, with stronger fMRI responses for motion towards versus away from the ROI. This effect was independent of the change in luminance. In Area V1 we found higher activity for high-contrast onsets and offsets near the ROI, but no significant differences between motion directions. We suggest that perceived final positions of moving objects are based on an interplay of predictive position representations in higher motion-sensitive retinotopic areas and offset transients in primary visual cortex.